Marketing Capabilities Model for Pharmaceutical Business in Thailand - Napassorn Kerdpitak, Chayanan Kerdpitak, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
There are few studies in the past which have worked on evaluating the capability of the marketing teams as the means of generating an effective strategy in terms of competiveness in the market and creation of advantage that is held by a firm in the market. However, the aim behind conducting this research is to find an effective mechanism or formula to have better performance in the export field, internationalization success, and marketing communication mainly by analyzing the role that is played by the marketing capabilities. Moreover, the researcher has mapped the relationship which exists between the capabilities and communication with the mediating impact of competitive strategy has also been evaluated in this research paper. The population of this study was the employees of different pharmaceutical firms of Thailand, and the sample was 300 entrepreneur of pharmaceutical business. The results and findings show that the impact of marketing capabilities has been favorable to enhance the export performance of the sector. Furthermore, the findings also indicate that the mediating variable of competitive strategy also positively mediates the relationship that exists between the variables of marketing capabilities and marketing communication. This study has significant implications on MC and export performance.